Study guides

Q: What is the answer to 4x plus 3 equals 9?

Write your answer...

Submit

Related questions

x=3

3+6x = 4x+9 6x-4x = 9-3 2x = 6 x = 3

4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2

The answer to the problem of 13 equals -4x plus 9 is x equals -1.

4x + 3y=9 x=0 y=3

4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.

x = -1/3

-4x + 3y = 9

4x

5x = 4x + 9 x = 9

99

(2x - 3)(4x + 9)(2x + 3) = (2x - 3)(2x + 3)(4x + 9) = [(2x)^2 - (3^2)](4x + 9) = (4x^2 - 9)(4x + 9) = (4x^2)(4x) + (4x^2)(9) - (9)(4x) - (9)(9) = 16x^3 + 36 x^2 - 36x - 81

X equals 2 :)

-5x + x + 9 = -4x + 12 -4x + 9 = -4x + 12 9 = 12 This equation has no solution.

3y = 4x + 9 -4x + 3y = 9 is the standard form

-6 + 4x + (9-2x) = -6 + 4x + 9 - 2x = [ 3 + 2x ]

(4x + 3)(4x + 3) (4x + 3)2

2x-3=4x+9 -2x-12=0 2x=-12 x=-6

x2 + 4x - 9 = 5x + 3 ∴ x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}

4x+5 = -9 4x = -9-5 4x = -14 x = -3.5

16x2-9

x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4

4x+9=25 4x=16 x=4

4x + 2 = 3x + 9 x + 2 = 9 x = 7

7x - 2 = 4x + 9 3x - 2 = 9 3x = 11 x = 11/3